A New Approach to Defining and Measuring Family Engagement in Early Childhood Education Programs - Terri J. Sabol; Teresa Eckrich Sommer; Amy Sanchez; Andrea Kinghorn Busby (SAGE Publishing, 2018)
Almost every state-level Quality Rating and Improvement System (QRIS) in the country includes family engagement as an indicator of early childhood education quality. Yet, most QRIS measure family engagement using a uniform, narrow set of parent involvement activities at the center. We propose an alternative approach that emphasizes a range of direct services for parents, including: (1) parenting classes, (2) family support services, (3) social capital activities, and (4) human capital services. In our proposed rating systems, states would assess how well centers address the highest ranked needs of families and employ evidence-based practices across one or more of the center-selected direct parent service categories. We explore the feasibility of this approach through a qualitative study (n = 14 centers) and case examples. We discuss how this new rating system could be used to monitor quality and as a tool for program improvement to support child development.